TECHNOLOGY FOR THE FORMATION OF PEDAGOGICAL TECHNIQUES - Z. Isakova; R. Meliboyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, a brief analysis of the methods of formation of pedagogical skills of teachers is described. Proposals were developed on the basis of analytical conclusions